Acute Kidney Injury Following Coronary Artery Bypass Grafting with Cardiopulmonary Bypass at Dr. Soetomo General Academic Hospital Surabaya: A Preliminary Study - Ghuraba Adi Surya; Kun Arifi Abbas (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: Acute Kidney Injury (AKI) is a significant cause of morbidity and mortality following common cardiac surgery. The most common cardiac surgery performed at Dr Soetomo General Academic Hospital Surabaya is coronary artery bypass grafting (CABG). Along with the increasing number of these procedures performed on subjects, Cardiopulmonary Bypass (CPB) has also grown in popularity, which is frequently associated with postoperative AKI. Objective: To investigate the incidence of postoperative AKI in subjects who had undergone a CABG procedure using the CPB technique. Materials and Methods: A retrospective study was conducted at Dr. Soetomo General Academic Hospital in Surabaya. All subjects who had CABG with CPB in 2019 were included in the study. The incidence of AKI was determined by comparing the creatinine serum level before and after surgery on days 0, 1, 2, 3, and >3 according to the AKIN criteria. Results and Discussion: The 68 subjects who underwent the CABG with CPB procedure were made up of 53 males (77.9%) and 15 females (22.1%). The average age of the subjects was 58.209.07. This study included 63 subjects (five subjects could not be evaluated due to incomplete data), and AKI was diagnosed in 44 of them using the AKIN criteria (69.8%). Postoperative AKI was reported in 14 subjects (22.2%) on day 0, 18 subjects (28.6%) on day 1 post-operation, and the same number of 6 subjects (9.5%) on day 2 and day 3 post-operation. None of them had AKI after the third post-operative day. Conclusion: More than 50 % of cases of post-CABG Acute Kidney Injury (AKI) occur at Dr. Soetomo General Academic Hospital, with the majority occurring on the first day after surgery.